Lithium secondary battery
By performing XRD and ICP analysis on lithium iron phosphate compounds, and selecting materials that meet specific conditions as the positive electrode active material, the energy density and quality uniformity problems in lithium secondary batteries are solved, and capacity improvement and manufacturing process simplification is achieved.
Patent Information
- Application Number
- CN202380059589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-14
AI Technical Summary
The lithium iron phosphate compounds used in lithium secondary batteries have low energy density and quality uniformity problems.
The lattice constants a, b and c of lithium iron phosphate compounds were measured by X-ray diffraction analysis (XRD), and the molar ratio of Li to Fe and doped element (M) was measured by ICP analysis, and lithium iron phosphate compounds that meet specific conditions were selected as the positive electrode active material.
The capacity and quality uniformity of lithium secondary batteries are improved, the initial capacity characteristics are improved, and the manufacturing process is simplified, avoiding the inconvenience of directly measuring electrochemical properties.
Smart Images

Figure CN119631196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium secondary battery, and more particularly to a lithium secondary battery containing a lithium iron phosphate compound as a positive electrode active material and a method for manufacturing the same. Background Art
[0002] Lithium secondary batteries are generally prepared by placing a separator between a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material to form an electrode assembly; inserting the electrode assembly into a battery case; injecting a non-aqueous electrolyte serving as a lithium ion transport medium, and then sealing the battery case. The non-aqueous electrolyte is generally composed of a lithium salt and an organic solvent capable of dissolving the lithium salt.
[0003] As positive electrode active materials for lithium secondary batteries, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, etc. are used. In particular, lithium iron phosphate compounds have excellent thermal stability to provide excellent life and safety, and are cheap, so they are widely used as positive electrode active materials for lithium secondary batteries. However, lithium iron phosphate compounds have lower energy density than other positive electrode active materials, resulting in lower capacity.
[0004] In addition, the stoichiometry or impurity content of lithium iron phosphate compounds depends on the initial synthesis state, storage conditions, etc. Therefore, when lithium iron phosphate compounds are applied to batteries, the quality uniformity decreases due to changes in initial charging capacity and life. Summary of the invention
[0005] Technical issues
[0006] One aspect of the present invention provides a lithium secondary battery that can improve the capacity and quality uniformity of the secondary battery by applying a lithium iron phosphate compound as a positive electrode active material in which the lattice constants a, b and c measured by X-ray diffraction analysis (XRD) meet specific conditions and the molar ratio of Li to iron and doping element (M) measured by ICP analysis meets a specific range.
[0007] Technical Solution
[0008] According to one aspect of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.
[0009] The positive electrode comprises a lithium iron phosphate compound represented by the following chemical formula 1, and
[0010] The L value of the lithium iron phosphate compound is 0.3926 to 0.3929, wherein the L value is represented by the following Mathematical Formula 1.
[0011] [Chemical formula 1]
[0012] Li 1-a [Fe 1-x M x ] 1-y PO 4-b A b
[0013] In the above chemical formula 1,
[0014] M is at least one selected from the group consisting of Mn, Ni, Co, Cu, Sc, Ti, Cr, V and Zn,
[0015] A is at least one selected from S, Se, F, Cl and I, and
[0016] Satisfied -0.5 <a<0.5、0≤x<1、-0.5<y<0.5、0≤b≤0.1、1.07≤(1-a) / (1-y)≤1.09。
[0017] [Mathematical formula 1]
[0018]
[0019] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0020] On the other hand, in the lithium iron phosphate compound, the molar ratio 1 / (1-y) of P to Fe and M is 1.02 to 1.10.
[0021] In addition, the lithium iron phosphate compound may also include a conductive coating.
[0022] According to another aspect of the present invention, there is provided a method for manufacturing a lithium secondary battery, the method comprising the following steps:
[0023] The lattice constants a, b and c of the lithium iron phosphate compound are measured by X-ray diffraction analysis, and the L value defined by the following mathematical formula 1 is measured;
[0024] The molar ratio of Li to Fe and doping element (M) of lithium iron phosphate compounds was measured by ICP analysis;
[0025] Selecting a lithium iron phosphate compound in which the L value meets a preset range and the molar ratio of Li to Fe and the doping element (M) is 1.07 to 1.09 as a positive electrode active material;
[0026] manufacturing a positive electrode containing a selected positive electrode active material;
[0027] manufacturing an electrode assembly including a positive electrode, a separator, and a negative electrode; and
[0028] The electrode assembly is housed in a battery case, and then an electrolyte is injected.
[0029] [Mathematical formula 1]
[0030]
[0031] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0032] Preferably, the preset range may be 0.3926 to 0.3929.
[0033] Beneficial Effects
[0034] The present invention measures the lattice constants a, b and c values by XRD analysis, measures the molar ratio of Li to Fe and a doping element (M) of a lithium iron phosphate compound by ICP analysis, and then uses the lithium iron phosphate compound in which the lattice constants a, b and c values and the molar ratio of Li to Fe and the doping element (M) meet specific conditions as a positive electrode active material, thereby improving the capacity characteristics of an LFP battery.
[0035] In addition, the method for manufacturing a lithium secondary battery of the present invention includes: performing XRD and ICP analysis on a lithium iron phosphate compound, and then selecting a lithium iron phosphate compound that meets specific conditions as a positive electrode active material based on the analysis results, thereby manufacturing a secondary battery with uniform quality without going through the inconvenient process of manufacturing the battery and directly measuring the performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a graph showing the initial charge capacity of the lithium secondary batteries manufactured in Examples 1 to 8 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0037] It should be understood that the terms or words used in this document and the claims of the present invention should not be understood to be limited to the meanings defined in commonly used dictionaries. It should also be understood that the words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant technical field and the technical ideas of the present invention, based on the inventor's ability to appropriately define the concepts of the words or terms to best describe the principles of the present invention.
[0038] In the present invention, the term "primary particle" refers to a particle unit in which no grain boundary is observed when observed in a field of view at a magnification of 5000 to 20000 using a scanning electron microscope. The term "average particle size of primary particles" refers to the arithmetic mean value calculated after measuring the particle size of primary particles observed in a scanning electron microscope image.
[0039] In the present invention, the term "average particle size D 50 " represents the particle size relative to 50% in the volume cumulative particle size distribution of the positive electrode active material powder. The average particle size D 50 Laser diffraction can be used to measure. For example, the average particle size D 50 It can be measured as follows: the positive electrode active material powder is dispersed in a dispersion medium; the dispersion medium is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves having a frequency of about 28 kHz and an output of 60 W to obtain a volume cumulative particle size distribution diagram; and the particle diameter at a volume cumulative 50% is calculated.
[0040] The mobility of lithium ions during charging / discharging of lithium secondary batteries is affected by the composition of the positive electrode active material and its lattice structure. Therefore, in order to keep the electrochemical properties (such as energy density and life) stable, it is necessary to apply a positive electrode active material with a small lattice structure change. However, the lattice structure of lithium iron phosphate compounds depends on the synthesis conditions and storage environment, so even if lithium iron phosphate compounds prepared by the same manufacturer are used, changes in capacity characteristics will occur. Therefore, in general, in order to carry out quality control, there is the inconvenience of preparing lithium secondary battery cells and then testing electrochemical performance.
[0041] The inventors conducted a large number of experiments to develop a secondary battery (hereinafter referred to as "LFP battery") using lithium iron phosphate compounds with excellent capacity characteristics and quality uniformity, and finally obtained a new parameter L correlated with the electrochemical properties of the LFP battery. Using the new parameter L, they discovered a way to manufacture LFP batteries with excellent initial capacity, thereby completing the present invention.
[0042] The parameter L may be defined by the following Mathematical Formula 1, where a, b, and c respectively represent lattice constants a, b, and c values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0043] [Mathematical formula 1]
[0044]
[0045] According to the research conducted by the present inventors, when a lithium iron phosphate compound in which the L value satisfies a specific range and the molar ratio of lithium to iron (Fe) and the doping element (M) satisfies a specific range is applied as the positive electrode active material, the LFP battery shows significantly improved initial capacity characteristics.
[0046] The L value and the molar ratio of lithium to iron (Fe) and doping element (M) are closely related to the initial capacity characteristics of the LFP battery, so by measuring the L value through XRD analysis of lithium iron phosphate compounds and measuring the Li / (Fe+M) molar ratio through ICP analysis, the initial capacity characteristics of the LFP battery can be predicted without manufacturing the battery. Therefore, a secondary battery with excellent quality uniformity can be manufactured without going through the inconvenient process of battery manufacturing and performance testing.
[0047] Hereinafter, the present invention will be described in detail.
[0048] Lithium secondary battery
[0049] First, a lithium secondary battery according to the present invention will be described.
[0050] The lithium secondary battery of the present invention comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, and the positive electrode comprises a lithium iron phosphate compound having an L value of 0.3926 to 0.3929 represented by Chemical Formula 1, wherein the L value is represented by the following Mathematical Formula 1.
[0051] [Mathematical formula 1]
[0052]
[0053] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0054] [Chemical formula 1]
[0055] Li 1-a [Fe 1-x M x ] 1-y PO 4-b A b
[0056] In the above chemical formula 1,
[0057] M is at least one selected from the group consisting of Mn, Ni, Co, Cu, Sc, Ti, Cr, V and Zn,
[0058] A is at least one selected from S, Se, F, Cl and I, and
[0059] Satisfied -0.5 <a<0.5、0≤x<1、-0.5<y<0.5、0≤b≤0.1、1.07≤(1-a) / (1-y)≤1.09。
[0060] (1) Positive electrode
[0061] The positive electrode according to the present invention includes a lithium iron phosphate compound as a positive electrode active material. Specifically, the positive electrode includes a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including the lithium iron phosphate compound.
[0062] In this case, the lithium iron phosphate-based compound may be represented by Chemical Formula 1 as follows.
[0063] [Chemical formula 1]
[0064] Li 1-a [Fe 1-x M x ] 1-y PO 4-b A b
[0065] In the above chemical formula 1,
[0066] M may be at least any one selected from the group consisting of Mn, Ni, Co, Cu, Sc, Ti, Cr, V and Zn, and
[0067] A may be at least any one selected from S, Se, F, Cl and I.
[0068] Furthermore, the above-mentioned a may satisfy -0.5≤a≤0.5, preferably -0.3≤a≤0.3, and more preferably -0.1≤a≤0.1.
[0069] Furthermore, the above x may satisfy 0≤x<1, preferably 0≤x≤0.8, and more preferably 0≤x≤0.7.
[0070] The above y may satisfy -0.5≤y≤0.5, preferably -0.3≤y≤0.3, and more preferably -0.1≤y≤0.1.
[0071] Furthermore, the above-mentioned b may satisfy 0≤b≤0.1, preferably 0≤b≤0.08, and more preferably 0≤b≤0.05.
[0072] In particular, considering the effect of improving conductivity and the resulting rate characteristics and capacity characteristics, the lithium iron phosphate compound can be, for example, LiFePO4, Li(Fe,Mn)PO4, Li(Fe,Co)PO4, Li(Fe,Ni)PO4 or a mixture thereof, preferably LiFePO4.
[0073] On the other hand, in the lithium iron phosphate compound, the molar ratio of Li to Fe and M (Li / (Fe+M)), that is, (1-a) / (1-y) in Chemical Formula 1, may be 1.07 to 1.09, preferably 1.08 to 1.09. When the Li / (Fe+M) ratio satisfies the above range, the initial capacity is shown to be particularly excellent.
[0074] In addition, in lithium iron phosphate compounds, the molar ratio of P to Fe and M (P / (Fe+M)), that is, 1 / (1-y) in Chemical Formula 1, can be 1.02 to 1.10, preferably 1.02 to 1.08, and more preferably 1.03 to 1.07. When the molar ratio of P to Fe and M is too small, the polyanion PO4 in the lattice structure is insufficient, and when the molar ratio of P to Fe and M is too large, the Li at the Fe site may increase, resulting in a state of excess Li, which may deteriorate the capacity characteristics.
[0075] On the other hand, the amounts (moles) of Li, Fe, M and P in the lithium iron phosphate compound are values measured by ICP analysis. ICP analysis can be performed as follows.
[0076] First, the lithium iron phosphate positive electrode active material was divided into vials (about 10 mg) and accurately weighed. Then, 2 ml of hydrochloric acid and 1 ml of hydrogen peroxide were added to the vial and dissolved at 100 ° C for 3 hours. Thereafter, 50 g of ultrapure water was added to the vial and 1000 μg / ml of scandium (0.5 ml) (internal standard) was accurately added to prepare the sample solution. The sample solution was filtered through a PVDF0.45 μm filter, and then the concentrations of Li, Fe, M and P components were measured using an ICP-OES (Perkin Elmer, AVIO500) instrument. If necessary, additional dilutions can be performed so that the concentration of the measured sample solution is within the calibration range of each component.
[0077] On the other hand, the L value of the lithium iron phosphate compound is 0.3926 to 0.3929, preferably 0.3926 to 0.3928, and more preferably 0.3926 to 0.39275, wherein the L value is represented by the following Mathematical Formula 1.
[0078] [Mathematical formula 1]
[0079]
[0080] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0081] According to the studies conducted by the present inventors, when a lithium iron phosphate-based compound having an L value satisfying the above range is used as a positive electrode active material, an excellent initial capacity can be obtained.
[0082] The L value is related to the Li concentration in the lattice structure of the lithium iron phosphate compound. When Li is removed from the lattice structure of the lithium iron phosphate compound, Fe 2+ O6 octahedral structure changes to Fe 3+ O6 octahedral structure, resulting in a decrease in the average Fe-O bond length, which in turn leads to a decrease in the lattice constants a and b. 2+ O6 octahedral structure changes to Fe 3+ When the PO4 tetrahedral structure is formed, the top Fe-01 is reduced, thereby rotating the PO4 tetrahedral structure around the b axis, resulting in an increase in the lattice constant c. That is, when the Li concentration in the LFP lattice structure decreases, the L value increases, and when the Li concentration increases, the L value decreases. The initial capacity of lithium iron phosphate compounds is determined by several factors such as the Li content and the amount of carbon coating, and according to the research conducted by the inventors, it is confirmed that among various factors, the Li concentration in the lattice structure represented by the L value is most closely related to the initial capacity. In particular, it is confirmed that when the L value is in the range of 0.3926 to 0.3929, the initial capacity is shown to be the highest.
[0083] The particle shape of the lithium iron phosphate compound is not particularly limited, but may be spherical in consideration of tap density.
[0084] In addition, the lithium iron phosphate compound may be composed of a single primary particle, or may be composed of secondary particles in which a plurality of primary particles are aggregated. In this case, the primary particles may be uniform or non-uniform. In the present invention, the primary particle refers to a primary structure of a single particle, and the secondary particle refers to an aggregate in which the primary particles are aggregated by physical or chemical bonding between the primary particles, i.e., a secondary structure.
[0085] On the other hand, lithium iron phosphate compounds may also contain a carbon coating. The structure of lithium iron phosphate compounds is very stable, but the electrical conductivity is relatively low. Therefore, it is expected to improve the electrical conductivity and resistance by coating the surface of lithium iron phosphate compounds with highly conductive carbon.
[0086] In addition, the average particle size (D 50 ) may be 1 μm to 20 μm, preferably 2 μm to 20 μm, and more preferably 2 μm to 15 μm. When the average particle size of the lithium iron phosphate compound is less than 1 μm, during the manufacture of the positive electrode, the dispersion is reduced due to agglomeration between particles, so the positive electrode characteristics may be reduced. In addition, when the average particle size (D 50) is greater than 20 μm, the mechanical strength and specific surface area may be reduced, the porosity between the lithium iron phosphate compound particles may excessively increase to cause a decrease in the tap density, or sedimentation may occur during the preparation of the positive electrode slurry.
[0087] On the other hand, when the lithium iron phosphate compound is a secondary particle, the average particle size of the primary particle can be 100 nm to 2 μm, preferably 100 nm to 1 μm, under the condition that the average particle size range of the secondary particle is satisfied. When the average particle size of the primary particle is less than 100 nm, the dispersibility will be reduced due to the agglomeration between the particles. When the average particle size is greater than 2 μm, the packing density may be reduced, resulting in a reduction in the capacity characteristics of the electrode.
[0088] On the other hand, the lithium iron phosphate compound may further include a conductive coating on its surface. The conductive coating is intended to improve the conductivity of the lithium iron phosphate compound, and may include any one or a mixture of two or more selected from carbon materials, metals, and conductive polymers. In particular, when a conductive coating of a carbon material is included, the conductivity can be effectively improved without significantly increasing the weight of the lithium iron phosphate compound.
[0089] The conductive coating layer may be formed according to a typical method for forming a coating layer, and the content relative to the total weight of the lithium iron phosphate compound may be 1 wt % to 7 wt %, more specifically 1 wt % to 5 wt %. When the amount of the conductive coating layer is too large, greater than 7 wt %, there is a problem in that the battery characteristics may be reduced due to the relative reduction of the LFP content, and when the amount of the conductive coating layer is less than 1 wt %, the effect of improving conductivity generated by the formation of the conductive layer may not be significant.
[0090] On the other hand, the positive electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can generally have a thickness of 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0091] On the other hand, the positive electrode active material layer may further include a conductive material, a binder, a dispersant, and the like in addition to the lithium iron phosphate-based compound.
[0092] In this case, the conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation, as long as it has electronic conductivity and does not cause chemical changes in the constructed battery. Specific examples thereof may include: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber and carbon nanotubes; metal powders or metal fibers such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 0.4 wt % to 10 wt %, preferably 0.4 wt % to 7 wt %, and more preferably 0.4 wt % to 5 wt % relative to the total weight of the positive electrode active material layer. When the amount of the conductive material satisfies the above range, excellent positive electrode conductivity and capacity may be achieved.
[0093] In addition, the binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0094] The content of the binder may be 1 wt % to 5 wt %, preferably 1.5 wt % to 5 wt %, more preferably 1.5 wt % to 4 wt %, and even more preferably 2 wt % to 4 wt %, relative to the total weight of the positive electrode active material layer. When the amount of the binder satisfies the above range, the adhesion between the current collector and the positive electrode active material layer is high, so there is no need to design a separate layer (e.g., bottom layer) to improve the adhesion, and even when the positive electrode loading is high (e.g., 400 mg / 25 cm 2 When the positive electrode has a capacity of more than 100 μm, the positive electrode adhesion can still be kept excellent to achieve excellent capacity and life.
[0095] The dispersant is intended to improve the dispersibility of lithium iron phosphate compounds, conductive materials, etc., for example, hydrogenated nitrile rubber (H-NBR) can be used, but the embodiments of the present invention are not limited thereto, and various dispersants that can improve the dispersibility of the positive electrode slurry can be used. Relative to the total weight of the positive electrode active material layer, the content of the dispersant can be 2% by weight or less, preferably 0.1 to 2% by weight, and more preferably 0.1 to 1% by weight. When the amount of the dispersant is too small, the effect of improving the dispersibility is not significant, and when the amount is too high, it may have an adverse effect on the battery performance.
[0096] On the other hand, the loading amount of the positive electrode according to the present invention can be 350 mg / 25 cm 2 Up to 2000 mg / 25 cm 2 , preferably 400 mg / 25 cm 2 Up to 1700 mg / 25 cm 2 , more preferably 450 mg / 25 cm 2 Up to 1000 mg / 25 cm 2 When the cathode loading meets the above range, the capacity can be greater than that of a typical LFP battery. In this case, the cathode loading is expressed as the amount of carbon dioxide in the cathode at 25 cm 2 The weight of lithium iron phosphate compounds contained in the area.
[0097] In addition, the porosity of the positive electrode is 25% to 60%, preferably 28% to 55%, more preferably 28% to 40%, still more preferably 28% to 35%, and more preferably 25% to 30%. When the positive electrode porosity is formed within the above range, both the energy density and the electrolyte impregnation can be maintained excellent. For LFP batteries, lithium iron phosphate compounds as positive electrode active materials have a small particle size, whereby the pore size in the positive electrode is small to cause the electrolyte impregnation performance to decrease, so LFP batteries preferably form a higher positive electrode porosity than batteries using other positive electrode active materials, but when the positive electrode porosity increases, the energy density decreases. Therefore, it is necessary to appropriately adjust the positive electrode porosity to maintain excellent energy density and electrolyte impregnation performance.
[0098] (2) Negative electrode
[0099] According to the present invention, the negative electrode may be a common negative electrode in the art, for example, the negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0100] The negative electrode can be prepared, for example, by coating a negative electrode slurry containing a negative electrode active material and optionally a binder and a conductive material onto a negative electrode collector and drying to form a negative electrode active material layer, and then calendering; or by casting the negative electrode slurry on a separate support, and then laminating the film obtained by peeling off the support on the negative electrode collector.
[0101] The negative current collector is not particularly limited as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, the following can be used: copper, stainless steel, aluminum, nickel, titanium, calcined carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. In addition, the negative current collector usually can have a thickness of 3 μm to 500 μm, and similar to the case of the positive current collector, fine irregularities can be formed on the surface of the negative current collector to improve the adhesion of the negative active material. For example, the negative current collector can be used in various forms such as film, sheet, foil, net, porous body, foam body, and non-woven fabric body.
[0102] The negative active material layer selectively contains a binder and a conductive material in addition to the negative active material.
[0103] As the negative active material, compounds capable of reversibly inserting and extracting lithium can be used. Specific examples thereof can include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi) metallic materials capable of forming an alloy with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; (semi) metal oxides capable of doping and undoping lithium such as SiO x (0 < x < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composite materials containing (semi) metallic materials and carbonaceous materials such as Si-C composite materials or Sn-C composite materials, and any one of them or a mixture of two or more thereof can be used. In addition, as the negative active material, a lithium metal thin film can be used. In addition, as the carbon material, low-crystalline carbon, high-crystalline carbon, etc. can all be used. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be irregular, plate-shaped, flake-shaped, spherical, or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microsphere, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.
[0104] In addition, the binder and the conductive material can be the same as those described above for the positive electrode.
[0105] (3) Separator
[0106] In the present invention, the separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is generally used as a separator in a lithium secondary battery. In particular, a separator having a high moisture retention capacity for electrolytes and low resistance to the movement of electrolyte ions is preferred. Specifically, a porous polymer film, such as a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, can be used; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of glass fibers, polyethylene terephthalate fibers, etc. having a high melting point. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be optionally used in a single-layer or multilayer structure.
[0107] (4) Electrolytes
[0108] The electrolyte used in the present invention can be any organic liquid electrolyte, inorganic liquid electrolyte, solid polymer electrolyte, gel polymer electrolyte, solid inorganic electrolyte, molten inorganic electrolyte, etc. that can be used to prepare lithium secondary batteries, but is not limited thereto.
[0109] For example, the electrolyte may include an organic solvent and a lithium salt.
[0110] Any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol. Among these solvents, carbonate solvents are preferred, and more preferably a mixture of a cyclic carbonate (such as ethylene carbonate or propylene carbonate) having high ion conductivity and high dielectric constant and a linear carbonate compound (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) having low viscosity can improve the charge / discharge performance of the battery.
[0111] Lithium salt can be used without particular limitation, as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, as lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. Lithium salt can be used in a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can be effectively moved.
[0112] In addition to the electrolyte components, the electrolyte may also contain additives for improving the life characteristics of the battery, preventing the battery capacity from decreasing, and increasing the battery discharge capacity. As additives, various electrolyte additives used in lithium secondary batteries can be used, and for example: halogenated carbonate compounds such as fluoroethylene carbonate; nitrile compounds such as succinonitrile; sultone compounds such as 1,3-propane sultone and 1,3-propylene sultone; carbonate compounds such as vinylene carbonate; or a combination thereof, but the additive is not limited thereto. In this case, the content of the additive may be 0.1 wt % to 10 wt %, preferably 0.1 wt % to 5 wt %, relative to the total weight of the electrolyte.
[0113] As described above, the lithium secondary battery of the present invention has a larger charging capacity than conventional batteries. Specifically, relative to the theoretical capacity of lithium iron phosphate (170 mAh / g), the first charging capacity of the lithium secondary battery according to the present invention when charged at 0.1C until 3.7 V can be 93% to 100% of the theoretical capacity, preferably 93% to 98%, and more preferably 94% to 97%.
[0114] Specifically, relative to the theoretical capacity of lithium iron phosphate (170 mAh / g), the first charging capacity of the lithium secondary battery according to the present invention when charged to 3.7 V at 0.1C can be 158 mAh / g to 170 mAh / g, preferably 158 mAh / g to 167 mAh / g, and more preferably 159 mAh / g to 165 mAh / g.
[0115] <Method for Manufacturing Lithium Secondary Battery>
[0116] Hereinafter, a method of manufacturing a lithium secondary battery according to the present invention will be described.
[0117] The method for manufacturing a lithium secondary battery according to the present invention comprises the following steps:
[0118] (1) measuring the lattice constants a, b and c of the lithium iron phosphate compound by X-ray diffraction analysis, and measuring the L value defined by the following mathematical formula 1;
[0119] (2) measuring the molar ratio of Li to Fe and the doping element M in the lithium iron phosphate compound by ICP analysis;
[0120] (3) selecting a lithium iron phosphate compound in which the L value satisfies a preset range and the molar ratio of Li to Fe and the doping element M is 1.07 to 1.09 as a positive electrode active material;
[0121] (4) manufacturing a positive electrode containing a positive electrode active material of a selected color;
[0122] (5) manufacturing an electrode assembly including a positive electrode, a separator and a negative electrode; and
[0123] (6) The electrode assembly is housed in a battery case and then the electrolyte is injected.
[0124] [Mathematical formula 1]
[0125]
[0126] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0127] (1) X-ray diffraction analysis method
[0128] First, the lattice constants a, b, and c of the lithium iron phosphate compound were measured by X-ray diffraction analysis.
[0129] In this case, X-ray diffraction analysis was performed using a Bruker D8 Endeavor instrument as follows.
[0130] First, the powder was placed in the center groove of a general powder holder or a small amount of powder holder, depending on the amount of sample to be tested, and a glass slide was used to ensure that the sample height matched the edge of the holder and the sample surface was uniform. Then, the fixed divergence slit was set to 0.3 according to the sample size, and the 2θ area was measured every 0.016°. The phases present in the sample in the range of 10° to 120° were Rietveld refined using the complete structure model.
[0131] Then, the lattice constants a, b, and c of the lithium iron phosphate-based compound measured by X-ray diffraction analysis are substituted into Mathematical Formula 1 to measure the L value.
[0132] [Mathematical formula 1]
[0133]
[0134] In the above Mathematical Formula 1, a, b, and c are lattice constant values of the lithium iron phosphate-based compound measured by X-ray diffraction (XRD).
[0135] As described above, the electrochemical performance of the LFP battery is closely related to the L value shown in Mathematical Formula 1. Therefore, by performing XRD analysis on the lithium iron phosphate compound to measure the lattice constants a, b and c, and then using the measured values to determine the parameter L value shown in Mathematical Formula 1, a positive electrode active material that can achieve the desired performance of the lithium secondary battery cell can be selected without going through the inconvenient process of manufacturing the battery and directly measuring the performance.
[0136] (2) ICP analysis method
[0137] In addition, the molar ratio of each component in the lithium iron phosphate compound is measured by ICP analysis. ICP analysis can be performed as follows.
[0138] First, the lithium iron phosphate positive electrode active material was divided into vials (about 10 mg) and accurately weighed. Then, 2 ml of hydrochloric acid and 1 ml of hydrogen peroxide were added to the vial and dissolved at 100 ° C for 3 hours. Thereafter, 50 g of ultrapure water was added to the vial and 1000 μg / ml of scandium (0.5 ml) (internal standard) was accurately added to prepare the sample solution. The sample solution was filtered through a PVDF0.45 μm filter, and then the concentrations of Li, Fe, M and P components were measured using an ICP-OES (Perkin Elmer, AVIO500) instrument. If necessary, additional dilutions can be performed so that the concentration of the measured sample solution is within the calibration range of each component.
[0139] (3) Selection of positive electrode active materials
[0140] Then, a lithium iron phosphate-based compound in which the L value measured by the above Mathematical Formula 1 satisfies a preset range and a molar ratio of Li to Fe and a doping element (M) is 1.07 to 1.09 is selected as a positive electrode active material.
[0141] In this case, the preset range can be appropriately selected in consideration of the electrochemical properties of the LFP battery to be manufactured, for example, the preset range can be 0.3926 to 0.3929, preferably 0.3926 to 0.39285. When a lithium iron phosphate compound having an L value and a molar ratio of Li to Fe and a doping element (M) satisfying the above range is applied as a positive electrode active material, the initial capacity characteristics of the LFP battery are shown to be excellent.
[0142] (4) Preparation of positive electrode
[0143] Then, a positive electrode containing the selected positive electrode active material is prepared.
[0144] In this case, in addition to using a lithium iron phosphate compound having an L value satisfying a preset range and a molar ratio of Li / (Fe+M) of 1.07 to 1.09 as a positive electrode active material, the positive electrode can be prepared according to a conventional method for manufacturing a positive electrode known in the art. For example, the positive electrode can be prepared in the following manner: a positive electrode active material, a binder, and a conductive material are mixed to prepare a positive electrode slurry, and then the positive electrode slurry is coated on a positive electrode collector and dried to form a positive electrode active material layer, and then rolled.
[0145] On the other hand, specific types and specifications of the positive electrode active material, the binder, and the conductive material are the same as those described above, and thus detailed descriptions are not provided.
[0146] (5) Manufacturing of electrode components
[0147] Then, an electrode assembly including the positive electrode, separator and negative electrode prepared as above is manufactured. The specific types and specifications of the negative electrode and separator are the same as those described above, so detailed description is not provided.
[0148] The electrode assembly can be manufactured by stacking a positive electrode, a separator and a negative electrode in sequence. There is no particular limitation on the form of the electrode assembly, and the electrode assembly can be a common electrode assembly known in the field of lithium secondary batteries, such as a wound electrode assembly, a stacked electrode assembly and / or a stacked folded electrode assembly.
[0149] (6) Manufacturing of secondary batteries
[0150] Then, the electrode assembly is housed in a battery case and an electrolyte is injected to manufacture a lithium secondary battery.
[0151] In this case, the battery case may be any general battery case known in the field of lithium secondary batteries, and for example, a cylindrical, square, or pouch-shaped battery case may be used without limitation, and the battery case is not particularly limited thereto.
[0152] On the other hand, the specific type and specification of the electrolyte are the same as those described above, and the electrolyte injection can be performed by a common electrolyte injection method known in the field of lithium secondary batteries.
[0153] Preferred Embodiments
[0154] Hereinafter, the present invention will be described in more detail through specific embodiments.
[0155] Experimental Example 1: Physical property measurement of lithium iron phosphate compounds
[0156] Eleven types of samples of lithium iron phosphate compound powders A to J were collected and subjected to XRD analysis to measure the L value. In addition, ICP analysis was performed to measure the Li / Fe molar ratio and the P / Fe molar ratio of the lithium iron phosphate compound powders A to J. In this case, the XRD analysis and the ICP analysis were performed by the above method.
[0157] The measurement results are shown in Table 1 below.
[0158]
[0159] Example 1
[0160] 95 parts by weight of sample C as a positive electrode active material, 2 parts by weight of carbon black as a conductive material, and 3 parts by weight of PVDF as a binder were mixed in a solvent of N-methylpyrrolidone to prepare a positive electrode slurry. The positive electrode slurry was coated on an aluminum current collector with a thickness of 15 μm, dried, and then rolled to prepare a positive electrode slurry with a loading of 500 mg / 25 cm 2 And the positive electrode has a porosity of 29%.
[0161] On the other hand, 95 parts by weight of artificial graphite as a negative electrode active material, 3 parts by weight of SBR and 1 part by weight of CMC as a binder, and 1 part by weight of carbon black as a conductive material were added to distilled water to prepare a negative electrode slurry. The negative electrode slurry was coated on a copper current collector having a thickness of 8 μm, dried and rolled to prepare a 240 mg / 25 cm 2 And the porosity of the negative electrode is 29%.
[0162] The positive electrode and negative electrode prepared as above were stacked together with a polyethylene separator to manufacture an electrode assembly, and then the electrode assembly was placed in a battery case, and an electrolyte in which 1M LiPF6 was dissolved in a solvent mixed with ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a volume ratio of 1:1:1 was injected to manufacture a lithium secondary battery.
[0163] Example 2
[0164] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample D was used instead of Sample C as the positive electrode active material.
[0165] Example 3
[0166] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample E was used instead of Sample C as the positive electrode active material.
[0167] Example 4
[0168] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample F was used instead of Sample C as the positive electrode active material.
[0169] Example 5
[0170] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample G was used instead of Sample C as the positive electrode active material.
[0171] Example 6
[0172] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample H was used instead of Sample C as the positive electrode active material.
[0173] Example 7
[0174] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample I was used instead of Sample C as the positive electrode active material.
[0175] Example 8
[0176] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample J was used instead of Sample C as the positive electrode active material.
[0177] Comparative Example 1
[0178] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample A was used instead of Sample C as the positive electrode active material.
[0179] Comparative Example 2
[0180] A lithium secondary battery was manufactured in the same manner as in Example 1, except that Sample B was used instead of Sample C as the positive electrode active material.
[0181] Experimental Example 2
[0182] Relative to the theoretical capacity of lithium iron phosphate (170 mAh / g), the lithium secondary batteries manufactured in Examples 1 to 8 and Comparative Examples 1 and 2 were charged at 0.1C to 3.7 V and then discharged at 0.1C to 2.5 V. Then, the lithium secondary batteries were charged at 0.1C to 3.7 V to measure the first charge capacity. The measurement results are shown in Figure 1 middle.
[0183] Figure 1It is shown that the lithium secondary batteries of Examples 1 to 8 using lithium iron phosphate compounds C to J having an L value of 0.3926 to 0.3929 and a Li / Fe molar ratio of 1.07 to 1.09 have a high initial capacity of 159 mAh / g, while the lithium secondary battery of Comparative Example 1 using lithium iron phosphate compound A having an L value greater than 0.3929 and a Li / Fe molar ratio less than 1.07 and the lithium secondary battery of Comparative Example 2 using lithium iron phosphate compound B having an L value less than 0.3926 and a Li / Fe molar ratio less than 1.07 have low initial capacities.
Claims
1. A lithium secondary battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, The positive electrode comprises a lithium iron phosphate compound represented by the following chemical formula 1, and The L value of the lithium iron phosphate compound is 0.3926 to 0.3929, wherein the L value is represented by the following mathematical formula 1: [Chemical formula 1] Li 1-a [Fe 1-x M x ] 1-y NIGHT 4-b A b Wherein in the above chemical formula 1, M is at least one selected from the group consisting of Mn, Ni, Co, Cu, Sc, Ti, Cr, V and Zn, A is at least one selected from S, Se, F, Cl and I, and Satisfied -0.5 <a<0.5、0≤x<1、-0.5<y<0.5、0≤b≤0.1、1.07≤(1-a) / (1-y)≤1.09, [Mathematical formula 1] In the above mathematical formula 1, a, b and c are lattice constant values of the lithium iron phosphate compound measured by X-ray diffraction (XRD). 2 . The lithium secondary battery according to claim 1 , wherein in the lithium iron phosphate compound, a molar ratio 1 / (1-y) of P to Fe and M is 1.02 to 1.
10. 3 . The lithium secondary battery according to claim 1 , wherein the lithium iron phosphate-based compound further comprises a conductive coating.
4. The lithium secondary battery according to claim 1, wherein the positive electrode loading is 350 mg / 25 cm 2 Up to 2000mg / 25 cm 2 . 5 . The lithium secondary battery according to claim 1 , wherein the positive electrode has a porosity of 25% to 60%. 6 . The lithium secondary battery according to claim 1 , wherein relative to the theoretical capacity (170 mAh / g) of lithium iron phosphate, the first charge capacity of the lithium secondary battery when charged at 0.1C to 3.7 V is 93% to 100% of the theoretical capacity.
7. A method for manufacturing a lithium secondary battery, the method comprising the following steps: The lattice constants a, b and c of the lithium iron phosphate compound are measured by X-ray diffraction analysis, and the L value defined by the following mathematical formula 1 is measured; Measuring the molar ratio of Li to Fe and the doping element (M) of the lithium iron phosphate compound by ICP analysis; Selecting a lithium iron phosphate compound as a positive electrode active material in which the L value meets a preset range and the molar ratio of Li to Fe and the doping element (M) is 1.07 to 1.09; manufacturing a positive electrode containing a selected positive electrode active material; manufacturing an electrode assembly including the positive electrode, a separator and a negative electrode; and The electrode assembly is housed in a battery case and then an electrolyte is injected. [Mathematical formula 1] In the above mathematical formula 1, a, b and c are lattice constant values of the lithium iron phosphate compound measured by X-ray diffraction (XRD). The method according to claim 7 , wherein the preset range is 0.3926 to 0.3929.